Consumer culture theory - Bajde, Domen; Kjeldgaard, Dannie; Belk, Russell W. (Research in consumer behavior, 2019)
The twentieth volume of Research in Consumer Behaviorpresents twelve chapters, selected from the best papers submitted at the 13th annual Consumer Culture Theory Conference 2018. The book explores three narrative lines that were prevalent during the conference: 'Objects and their doings', 'Glocalization', and 'Constituting Markets'.